New Advanced Placement course designed to broaden access promotes participation and demographic diversity in computer science education - Daniela Ganelin; Thomas S. Dee (Proceedings of the National Academy of Sciences, 2025)
Advanced Placement (AP) provides college-level courses to over 1 million US secondary students annually. Black, Hispanic, and female students have historically been underrepresented in AP Computer Science (CS). A new, broadly focused course—AP CS Principles—launched nationally in 2016–17 with the goal of increasing student participation and diversity. We examine its effects on AP CS participation. Combining publicly available sources, we assemble a panel dataset of annual AP exam-taking and course offerings from 2006–07 to 2020–21 at Massachusetts high schools. Using synthetic difference-in-differences, we estimate that offering the new course led to 16 additional yearly AP Computer Science exams per school, more than tripling baseline exam counts for the average adopting school. Exam counts among female and Black or Hispanic students more than quadrupled. The new exams were concentrated in AP Computer Science Principles, with no statistically significant reduction in exam counts for the preexisting AP CS course. We also estimate that offering the new course increased schools’ probability of having any AP CS exam participation by 29 percentage points, with larger gains for female and Black or Hispanic students. We find some evidence of positive spillover effects on several other AP courses. The results suggest the promise of course design and availability in promoting engagement and diversity in advanced STEM education.